Semi-numerical modelling of an n-channel irradiated MOSFET - Dasgupta S.; Chakrabarti P. (My University, 2025)
A semi-numerical model of a metal-oxide-semiconductor field effect transistor (MOSFET) has been developed for theoretical examination of the effect of ionizing radiation on the characteristics of the device. The present model utilizes the radiation-induced changes in the flat-band voltage to estimate the change in the surface charge carrier concentration which in turn changes the mobility of the surface channel and affects the source-to-drain current. For the first time a model of an irradiated MOSFET has been presented that incorporates the effect of both transverse and longitudinal electric fields in the transport of the carriers in the surface channel. The present model can also be used to determine the characteristics of the device in the pre-irradiated condition. The validity of the model has been established by comparing and contrasting the results in the pre-irradiated condition with those obtained using other models, including two-dimensional models. The results obtained on the basis of our model are compared with reported experimental results and also a SPICE (Level 3) model in the post-irradiated condition. It is found that our model gives a better fit to the reported experimental results as compared with SPICE models. The present model is expected to yield fairly accurate results for estimation of ID-VD characteristics and the transfer characteristics, even for a short channel device.